(untitled) (Journal of Environmental Bioremediation and Toxicology, 2021)
Obesity and diabetes mellitus are documented major risk factors for maternal and fetal health complications. Maternal lipid metabolism is greatly changed when pregnancy is complicated with obesity and diabetes mellitus. The effects of maternal obesity on placental lipid metabolism are not fully understood and thereby needs to be elucidated. Our objective is to study the lipid metabolism in the placenta of normal weight, overweight/obese and diabetic women, and to assess placental, maternal and cord serum triglycerides (TG). The term placentae, maternal and cord blood were collected from three (3) normal weight, three (3) overweight/obese and two (2) diabetic women during elective caesarean sections. The total lipid content of the placenta was measured using the Folch method. Lipolysis assay was carried out in placental tissue explant using an optimized method. Triglyceride levels of placental tissue, maternal, and cord serum were measured using a commercial reagent kit. The Placental total lipid (mg/500mg placental tissue) deposition was highest in the overweight (35.7±0.5), followed by diabetic (30.7±3.4) women, while both these groups had significantly higher (P<0.05) lipid contents than normal-weight women (19.6±3.9). However, the placental lipolysis among the three groups did not differ. The maternal-to-placental-to-cord TG ratio of the overweight women was 22:2:2, while it was 19:2:4 in diabetic and 16:2:1 in normal-weight women. Our study implies that although maternal obesity and diabetes affect placental lipid deposition, they may not have a notable effect on placental lipolysis. However, cord TG and maternal-to-cord TG ratio were markedly high among diabetic women.